The Effectiveness of the Eco Rocket Media-Assisted Inquiry Learning Model on Student Learning Outcomes - Defriel Maulana Dinnansyah; Ratna Dewi; Maya Rahayu (CV. Edujavare Publishing, 2026)
This research is based on the low participation and learning outcomes of students due to IPAS learning which is still dominated by lecture methods. This study aims to determine the effectiveness of the Eco Rocket-media-assisted guided inquiry learning model on student learning outcomes on Newton's Law III material in grade V of SDN Pengampelan. The research uses a quantitative approach with a quasi-experimental method (Quasi Experimental DeSign) in the form of a Nonequivalent Control Group DeSign. The study sample amounted to 52 students divided into VA class (experimental group, n=26) and VB class (control group, n=26), determined by saturated sampling technique. Data were collected through a multiple-choice test of 20 questions that had been tested for validity, reliability, difficulty, and differentiating power, and then analyzed using the Shapiro-Wilk normality test, the Levene's Test homogeneity test, the N-Gain test, and the Independent Sample t-Test hypothesis test. The results showed that the average score of the experimental class increased from 57.88 (pretest) to 79.23 (posttest), with an N-Gain of 51.38% (medium category), while the control class only increased from 54.62 to 55.96, with an N-Gain of 5.41% (low category). The Independent Sample t-Test yields a Sig value. (2-tailed) of 0.000 (<0.05), so H0 is rejected and Ha is accepted. It was concluded that the Eco Rocket-media-assisted guided inquiry learning model has proven to be effective and significantly improve student learning outcomes on Newton's III Law material compared to conventional learning.